Comparison of aerobic fitness between attention deficit hyperactivity disorder (ADHD) and normal male children aged 7 to 10 years old / Mohamad Hafiz Mohamad Khani - Mohamad Khani, Mohamad Hafiz (Faculty of Sport Science and Recreation, 2016)
Continuous active physical activities may contribute to better aerobic fitness. ADHD children tend to be hyperactive such as running, jumping, climbing and interrupting in all activities and this factor hypothesized contributes to aerobic fitness. This study 'was conducted to investigate aerobic fitness level between ADHD and normal male children, and to compare the aerobic fitness level of ADHD and normal male children according to the V02max normative. 35 ADHD and normal male children were recruited in the study. The V02max parameter was measured for two different categories of children which are ADHD and normal male children. The independent variable (IV) representing by ADHD and normal children, and dependent variable (DV) was V02max. Subjects were tested using 20 meter multi-stage shuttle run test and levels of the test were recorded to identify V02max. Subjects aged ranges between 7 to 10 years old. The results showed aerobic fitness level has no significant difference between ADHD and normal male children. Meanwhile, V02max normative also has no significant difference between both categories. Thus, null hypotheses were accepted